2022
DOI: 10.3390/metabo12020121
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Assay of Honeysuckle for Heat-Clearing Based on Metabolites and Metabolomics

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs), such as cyclooxygenase (Cox)-1/2 inhibitor, have emerged as potent antipyretics and analgesics. However, few herbs with Cox-1/2 inhibitory activity are commonly used for heat-clearing in China. Although these are known to have antipyretic activity, there is a lack of molecular data supporting their activity. Using the traditional Chinese medicine herb honeysuckle (Hon) as an example, we explored key antipyretic active compounds and their mechanisms of action by as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(30 reference statements)
0
9
0
Order By: Relevance
“… 2003 ; Blomqvist and Engblom 2018 ; Wang et al. 2022 ). Furthermore, we validated the predicted results of the network pharmacology by conducting an in vivo experiment, which showed that ZXP interfered with LPS-induced fever via inhibition of the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 2003 ; Blomqvist and Engblom 2018 ; Wang et al. 2022 ). Furthermore, we validated the predicted results of the network pharmacology by conducting an in vivo experiment, which showed that ZXP interfered with LPS-induced fever via inhibition of the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, treatment with an Sirtuin 1 (SIRT1) inhibitor (EX-527) partially abolished the inhibitory effect of gentiopicroside (40, 80 mg/kg) on ovalbumininduced airway inflammation, suggesting that the anti-inflammatory effect of gentiopicroside might be achieved by regulation of the SIRT1/NF-κB p65 signaling pathway (Zou et al, 2021). Wang, Quan, et al, 2022, Wang, Tian, et al, 2022 kg, ip) can increase the expression of SIRT1, and its protective effects on LPS-induced acute liver injury (ALI) can be reversed by the SIRT1 inhibitor EX-527 (Wang et al, 2021). Zhang et al demonstrated that the potent anti-inflammatory effect of sweroside (10 μg/mL for Rat chondrocytes) is mediated in part by suppression of the NF-κB and mammalian target of rapamycin (mTOR) C1 signaling pathways (Zhang, Gao, et al, 2019;Zhang, Wang, et al, 2019).…”
Section: S Chirayita Can Inhibit the Release Of Pro-inflammatory Fact...mentioning
confidence: 99%
“…Additional studies are needed to elucidate the detailed molecular mechanism and its potential in treating gastritis (Chang et al, 2021). Additionally, their anticonvulsant agent (Vaijanathappa et al, 2020), lung protection (Wang et al, 2021; Yao et al, 2016), antinociception (Jaishree et al, 2009), and antipyretic activity (Wang, Quan, et al, 2022; Wang, Tian, et al, 2022) have also been demonstrated. In a conclusion, based on the diverse pharmacological activities of Swertia L., the incidental action and molecular mechanisms should be primarily ascertained and succedent further illuminated.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…et al, 2017a ). Empirical research has underscored the efficacy of chlorogenic acid in ameliorating inflammatory ailments, attributing this to its multifaceted targeting of inflammatory pathways and its diminished propensity for drug resistance ( Wang et al, 2022a ; Fumiere et al, 2022 ; Feng et al, 2023 ). Specifically, chlorogenic acid can attenuate cardiac and cerebral afflictions triggered by inflammation and oxidative stress, conferring cardiovascular and cerebrovascular protective effects ( Wang et al, 2020a ; Liu et al, 2022 ; Zheng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%